Association between number and type of different ACPA fine specificities with lung abnormalities in early, untreated rheumatoid arthritis. Issue 2 (10th September 2020) - Joshua, Vijay; Hensvold, Aase Haj; Reynisdottir, Gudrun; Hansson, Monica; Cornillet, Martin; Nogueira, Leonor; Serre, Guy; Nyren, Sven; Karimi, Reza; Eklund, Anders; Sköld, Magnus; Grunewald, Johan; et al.
Abstract : Background: Rheumatoid arthritis (RA)-associated anticitrullinated protein/peptide antibodies (ACPA) might originate at mucosal sites such as the lungs. We aimed to examine the relationship between the ACPA repertoire and lung abnormalities on high-resolution CT (HRCT) in patients with earlyuntreated RA. Methods: 106 patients with newly diagnosed untreated RA were examined with HRCT of the lungs. Blood samples were analysed for presence of rheumatoid factor (RF) and ACPA using either a CCP2 detection kit or an immunochip containing 10 different citrullinated peptides. Association between HRCT findings and the antibody repertoire was assessed by logistic regression analysis. Results: The number (%) of patients with HRCT abnormalities was 58 (54.7%) for parenchymal abnormalities and 68 (64.2%) for airway abnormalities. CCP2 IgG, RF IgA and antibodies against citrullinated fibrinogen were associated with the presence of parenchymal lung abnormalities. Interestingly, a high number of ACPA fine specificities gave a high risk of having parenchymal lung abnormalities at the time of RA diagnosis. No significant signals were identified between ACPA specificities and risk for airway abnormalities. Conclusions: The presence of RF and ACPAs (especially against citrullinated fibrinogen peptides) as well as high number of ACPAs fine specificities are associated with parenchymal lung abnormalities in patients with early, untreated RA. This provides further support for an important pathogenic link between the lung and systemic autoimmunity, contributing to RA development.